Kebahagiaan Menurut Hamka dan Relavansinya terhadap Upaya Mengatasi Mental Distress - Darmawati Darmawati; Abdullah Firdaus; Jaya Jaya (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study, titled “Happiness According to Hamka and Its Relevance to Efforts to Overcome Mental Distress,” is motivated by the increasing mental strain experienced by modern society, which is reflected in rising levels of stress, anxiety, loss of life meaning, and various forms of depression. These symptoms indicate a deeper spiritual and emotional imbalance that cannot be resolved solely through clinical approaches, but requires insights from philosophical and religious thought. The purpose of this research is to reexamine Hamka’s concept of happiness and identify its relevance in supporting efforts to reduce mental distress in contemporary life. Using a qualitative-descriptive method with a library research approach, this study reviews Hamka’s key writings such as Tasawuf Modern, Falsafah Hidup, and Lembaga Budi alongside literature on psychology and mental health. Through a hermeneutic-philosophical analysis, the study finds that Hamka defines happiness as inner tranquility rooted in faith, sincerity, and spiritual connection with God, rather than material satisfaction or outward pleasures. He emphasizes that true happiness is achieved when intellect, emotion, and faith interact harmoniously, allowing individuals to manage desires, accept destiny, and uphold moral awareness. This perspective is highly relevant for addressing mental distress today, as Hamka highlights the importance of spiritual strengthening and purification of the soul as forms of internal healing capable of fostering resilience and emotional stability.